2007
DOI: 10.3141/1998-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polyphosphoric Acid-Modified Asphalt Binders with Straight and Polymer-Modified Materials

Abstract: This paper discusses the effects of polyphosphoric acid (PPA) modification on asphalt binders. Findings are compared with those for straight and polymer-modified materials of similar grades. The effect of PPA modification was investigated by means of conventional protocols as well as three new binder tests developed in Ontario, Canada. The compact tension test and the extended bending beam rheometer protocol were used to investigate low-temperature performance properties. The double edge-notched tension test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 6 publications
(11 reference statements)
0
26
0
4
Order By: Relevance
“…Bagampadde et al [42] showed that Styrene Butadiene Styrene (SBS) copolymer significantly enhanced moisture resistance of slag aggregates in harsh desert environments. Moreover, bitumen modified with SBS in conjunction with polyphosphoric acid (PPA) positively affected wettability performance and increased binder stability during long-time storage at elevated temperatures [43][44][45][46]. For example, PPA added to bitumen in a few wt.…”
Section: Appl Sci 2017 7 524 5 Of 10mentioning
confidence: 99%
“…Bagampadde et al [42] showed that Styrene Butadiene Styrene (SBS) copolymer significantly enhanced moisture resistance of slag aggregates in harsh desert environments. Moreover, bitumen modified with SBS in conjunction with polyphosphoric acid (PPA) positively affected wettability performance and increased binder stability during long-time storage at elevated temperatures [43][44][45][46]. For example, PPA added to bitumen in a few wt.…”
Section: Appl Sci 2017 7 524 5 Of 10mentioning
confidence: 99%
“…The addition of PPA in modified asphalts can also decrease the amount of polymer, reducing costs [8,9] . Related to the rheological properties, a system of PAC + EBGMA + PPA showed a very high deformation recovery and a very low non-recoverable compliance (J nr ) values, as well presented more resistance when subjected to a sudden increase in stress level [5] .…”
Section: Modification Of Thermal and Rheological Behavior Of Asphalt mentioning
confidence: 99%
“…Concerns have been raised by some researchers about the actual performance characteristics of the last polymer, PPA. These concerns include reversibility of the stiffening effect of PPA on asphalt binders and interactions with other additives in the mixtures such as hydrated lime [1]. Several grades of phosphoric acid containing different amounts of orthophosphoric acid are commercially available.…”
Section: Introductionmentioning
confidence: 99%